2017
DOI: 10.1016/j.aninu.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and hematology of Djallonké rams fed haulms of four varieties of groundnut ( Arachis hypogaea L.)

Abstract: The study was conducted to assess the chemical composition of the haulms of 4 dual-purpose groundnut (Arachis hypogaea L.) varieties and their effects on the growth and hematology of Djallonké rams. The groundnut varieties were ICGV 97049 (Obolo), ICGX SM 87057 (Yenyawoso), RMP 12 (Azivivi) and Manipinta. Rams (live weight 15.0 ± 3.0 kg) were randomly assigned to 4 sole groundnut haulm meal (GHM) treatments, with 4 rams each in an individual pen per treatment (total n = 16 rams). Samples of the groundnut haulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…Etela and Dung (2011) have shown that all nutrients digestibility is affected by the variety of the groundnut haulms used. This finding is contrary to that of Ansah et al (2017). According to these authors, the variety had no effect on the digestibility of the groundnut haulms nutrients they tested.…”
Section: Haulms Digestibilitymentioning
confidence: 59%
See 1 more Smart Citation
“…Etela and Dung (2011) have shown that all nutrients digestibility is affected by the variety of the groundnut haulms used. This finding is contrary to that of Ansah et al (2017). According to these authors, the variety had no effect on the digestibility of the groundnut haulms nutrients they tested.…”
Section: Haulms Digestibilitymentioning
confidence: 59%
“…(2017) and Ansah et al (2017). By contrast, in the studies of Etela and Dung (2011) and Ahounou et al (2017b), the variety did not have any effect on the TCP content.…”
Section: Chemical Composition and Nutritional Values Of Haulmsmentioning
confidence: 86%
“…Likewise, the emanation of enteric methane was found to be affected by diet quality; increased lignin produces higher emission and vice versa (O'Hara et al, 2003). The growth of ruminants is influeneced positively when more gross energy is conserved as a result of lower methane emission (Ansah et al, 2017). In the present study, methane was not quantified, but may be a contributor to differences in utilization of nutrients.…”
Section: Growth Performance For Yankasa Rams Fed Experimental Dietsmentioning
confidence: 75%
“…The higher weight gain recorded in this study may be an indication of better nutrient utilization from the groundnut shells. This suggest that in order to achieve greater live weight gains in growing rams, the level of supplementation made to the group of animals receiving UTGNS and LGNS diets is adequate (Ansah et al, 2017;Khan et al, 2017). It may also be as a result that the rams fed UTGNS and LGNS had a better nutrient absorption and utilization which resulted in a significantly higher weight gain and daily weight gain as compared to those fed UGNS or ULGNS (McDonald et al, 2010).…”
Section: Growth Performance For Yankasa Rams Fed Experimental Dietsmentioning
confidence: 99%
See 1 more Smart Citation